Effects of Losartan on high glucose-induced bone marrow sources of macrophages and the relationship of angiotensin Ⅱ type 1 receptor with renal pathological damage - JIANG Xiao; WU Yong-gui (Linchuang shenzangbing zazhi)
Objective To explore the relationship between renal injury and angiotensin Ⅱ type 1 receptor(AT1R) expression and macrophage infiltration in patients with diabetic nephropathy(DN) and to investigate the regulatory effect of ATIR inhibitor losartan on macrophages. Methods The renopuncture samples of DN patients with different pathological stages were collected and the expression of AT1R and infiltration of CD68~+ macrophages were detected in the renal tissues by immunohistochemistry(IHC). The macrophage infiltration in renal tissues was also compared between AT1R blocking drug-treated patients and control patients. In addition, high glucose-treated bone marrow-derived macrophages were used as an in vitro model. The AT1R blocker losartan was given to inhibit AT1R in macrophage in vitro. The purity and the expression of co-stimulatory molecules and cell phagocytic ability of macrophages were detected by flow cytometry. The mRNA and protein expression of inflammatory cytokines and subtyping markers of macrophage was determined by qRT-PCR and ELISA assays. NO production in cell culture supernatant was also measured by NO detection kit. Results The AT1R expression was significantly up-regulated in the renal tissue of patients with type III and IV DN as compared with the peritumorial control group(P<0.05). The macrophage infiltration in renal tissues from those patients was also greatly increased accordingly. In addition, the macrophage infiltration was repressed in ARB drugs-treated patients when compared with control group(P<0.05). The results of cell experiments further validated that the losartan intervention ameliorated high glucose-induced macrophages activation. Conclusions The AT1R expression and macrophage infiltration in renal tissues are positively correlated with the degree of renal injury of DN patients. The macrophage infiltration in renal tissues from DN patients could be repressed by ARB drugs.